Molecular profiling of stroma identifies osteopontin as an independent predictor of poor prognosis in intrahepatic cholangiocarcinoma. Issue 6 (17th October 2013) - Sulpice, Laurent; Rayar, Michel; Desille, Mireille; Turlin, Bruno; Fautrel, Alain; Boucher, Eveline; Llamas‐Gutierrez, Francisco; Meunier, Bernard; Boudjema, Karim; Clément, Bruno; Coulouarn, Cédric
<x xml:space="preserve">Abstract</x> Intrahepatic cholangiocarcinoma (ICC) is the second most common type of primary cancer in the liver. ICC is an aggressive cancer with poor prognosis and limited therapeutic strategies. The identification of new drug targets and prognostic biomarkers is an important clinical challenge for ICC. The presence of an abundant stroma is a histological hallmark of ICC. Given the well‐established role of the stromal compartment in the progression of cancer diseases, we hypothesized that relevant biomarkers could be identified by analyzing the stroma of ICC. By combining laser capture microdissection and gene expression profiling, we demonstrate that ICC stromal cells exhibit dramatic genomic changes. We identified a signature of 1, 073 nonredundant genes that significantly discriminate the tumor stroma from nontumor fibrous tissue. Functional analysis of differentially expressed genes demonstrated that up‐regulated genes in the stroma of ICC were related to cell cycle, extracellular matrix, and transforming growth factor beta (TGFβ) pathways. Tissue microarray analysis using an independent cohort of 40 ICC patients validated at a protein level the increased expression of collagen 4A1/COL4A1, laminin gamma 2/LAMC2, osteopontin/SPP1, KIAA0101, and TGFβ2 genes in the stroma of ICC. Statistical analysis of clinical and pathological features demonstrated that the expression of osteopontin, TGFβ2, and laminin in the stroma of ICC was significantly correlated with overall patient survival. More important, multivariate analysis demonstrated that the stromal expression of osteopontin was an independent prognostic marker for overall and disease‐free survival. Conclusion: The study identifies clinically relevant genomic alterations in the stroma of ICC, including candidate biomarkers for prognosis, supporting the idea that tumor stroma is an important factor for ICC onset and progression. (Hepatology 2013; 58:1992–2000)